Clinical and Pathophysiological Aspects of the Effect of Anticoagulants on Bone Tissue - O. D. Ostroumova; I. V. Goloborodova (Рациональная фармакотерапия в кардиологии, 2020)
Older age is associated with changes in bone metabolism, a loss in its mineral density and volume, and the development of osteoporosis. The high prevalence of atrial fibrillation and osteoporosis in older age groups causes their frequent combination in this category of patients. It is known that some diseases and/or drugs used to treat them, exacerbating the natural violation of bone metabolism, contribute to the progression of osteoporosis and its complications, which in turn can negatively affect the prognosis and quality of life of the patient. Anticoagulants, widely used in the treatment of thromboembolic complications and in the prevention of stroke, can have an adverse effect on bone metabolism. The purpose of this review was to generalize and systematize the available literature data regarding the features of the influence of various representatives of the anticoagulants group on bone tissue. The article analyzes the effects of unfractionated heparin, low molecular weight heparins, vitamin K antagonists, oral anticoagulants on bone metabolism, bone mineral density, and fractures. This review provides data from articles and reviews published through February 2020, inclusive, accumulated in the English-language database of medical and biological publications “PubMed”. The literature data confirm the negative effect of unfractionated heparin on bone tissue, with a violation of bone metabolism, a decreased bone mineral density and the development of fractures. Compared with unfractionated heparin, low molecular weight heparins appear to be safer, and vitamin K antagonists, having a significant effect on bone metabolism, contribute to a decreased bone mineral density, mainly in people who are on long-term (more than 1 year) therapy. Oral anticoagulants, having the mildest effect on bone metabolism, is associated with a lower (compared to other anticoagulants) risk of decreased bone mineral density and the development of fractures, and are recognized as the safest against bone tissue.